Dynamical evolution and chronology of the Hygiea asteroid family - Carruba, V. [UNESP]; Domingos, R. C.; Huaman, M. E. [UNESP]; Santos, C. R. dos [UNESP]; Souami, D. (Oxford University Press, 2014)
The asteroid (10) Hygiea is the fourth largest asteroid of the main belt, by volume and mass, and it is the largest member of its own family. Previous works investigated the long-term effects of close encounters with (10) Hygiea of asteroids in the orbital region of the family, and analysed the taxonomical and dynamical properties of members of this family. In this paper we apply the high-quality Sloan Digital Sky Survey-Moving Object Catalog data, fourth release (SDSS-MOC4) taxonomic scheme of DeMeo & Carry to members of the Hygiea family core and halo, we obtain an estimate of the minimum time and number of encounter necessary to obtain a 3 sigma (or 99.7 per cent) compatible frequency distribution function of changes in proper a caused by close encounters with (10) Hygiea, we study the behaviour of asteroids near secular resonance configurations, in the presence and absence of the Yarkovsky force, and obtain a first estimate of the age of the family based on orbital diffusion by the Yarkovsky and Yarkovsky-O'Keefe-Radzievsky-Paddack (YORP) effects with two methods.The Hygiea family is at least 2 Byr old, with an estimated age of T = 3200(-120)(+380) Myr and a relatively large initial ejection velocity field, according to the approach of Vokrouhlicky et al. Surprisingly, we found that the family age can be shortened by similar or equal to 25 per cent if the dynamical mobility caused by close encounters with (10) Hygiea is also accounted for, which opens interesting new research lines for the dynamical evolution of families associated with massive bodies. In our taxonomical analysis of the Hygiea asteroid family, we also identified a new V-type candidate: the asteroid (177904) (2005 SV5). If confirmed, this could be the fourth V-type object ever to be identified in the outer main belt.
Keywords: celestial mechanics; minor planets, asteroids: general; minor planets, asteroids: individual: Hygiea